Mining the Gut Microbiota for Microbial-Based Therapeutic Strategies in Cancer Immunotherapy - Li, Bolei; Gong, Tao; Hao, Yu; Zhou, Xuedong; Cheng, Lei (Frontiers in Oncology, 2021)
The past two decades witnessed a revolution in our understanding of host-microbial interactions that led to the concept of the super-organism consisting of a eukaryotic and a prokaryotic part. Owing to the critical role of gut microbiota in modulating the host immune system, it is not beyond all expectations that more and more evidence indicated the shift of gut microbiota influenced responses to numerous forms of cancer immunotherapy. Therapy targeting gut microbiota is becoming a promising strategy to improve cancer immunotherapy. In this review, we discuss the role of the gut microbiota in response to cancer immunotherapy, the mechanisms that the gut microbiota influences cancer immunotherapy, and therapeutic strategies targeting gut microbiota to improve cancer immunotherapy.